2015
DOI: 10.1007/s00464-015-4675-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus robotic-assisted Roux-en-Y gastric bypass: a retrospective, single-center study of early perioperative outcomes at a community hospital

Abstract: Our study, which is the first of its kind to analyze the operative and early perioperative outcomes between laparoscopic and robotic-assisted Roux-en-Y gastric bypass procedures in the US community hospital setting, indicates that both are comparable in terms of safety, efficacy, and operative and early perioperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 16 publications
2
16
1
Order By: Relevance
“…The operation times for RRYGB were significantly shorter than LRYGB, despite inclusion of the first procedures using the da Vinci Xi system. In contrast to our data, most studies report a longer operative time when using the robot [11,15,16,[21][22][23]29]. However, the operative time varies considerably between these publications, decreasing from a high of 245 min [13] to 108 min [16].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The operation times for RRYGB were significantly shorter than LRYGB, despite inclusion of the first procedures using the da Vinci Xi system. In contrast to our data, most studies report a longer operative time when using the robot [11,15,16,[21][22][23]29]. However, the operative time varies considerably between these publications, decreasing from a high of 245 min [13] to 108 min [16].…”
Section: Discussioncontrasting
confidence: 99%
“…Whether these statements are also valid for RRYGB remains to be shown. While most workgroups opted for a robotic hand-sewn anastomosis [8,11,12,[15][16][17][18][19]33], we kept to the well-established technique using the linear stapler. We decided to use an external linear stapler operated by the assistant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, although only limited data in terms of quality and quantity are currently available, it seems that robotically hand‐sewn anastomoses appear to compare favorably with the laparoscopically stapled technique in terms of leak rates . Nevertheless, several studies found higher leak rates for the robotic approach compared with the conventional laparoscopy, others found comparable leak rates in both groups . Moon et al reported leakage rates of 7.8% in 64 robotic consecutive cases compared to 0.5% in 206 laparoscopic cases .…”
Section: Resultsmentioning
confidence: 99%
“…The two largest published series including both a robotic experience of more than 300 cases reported a significantly lower leak rate in the handsewn robotic group compared with the stapled laparoscopic group . Nevertheless, several comparative series didn't confirm a better outcome for the robotic approach with comparable 30‐day results in terms of safety, efficacy and early postoperative outcomes . Some found even higher leak rates for the robotic technique …”
Section: Discussionmentioning
confidence: 99%